Prosumer-Based Optimization of Educational Building Grid Connected with Plug-in Electric Vehicle Integration using Modified Firefly Algorithm - Sandy, Yusdiar; Priyadi, Ardyono; Lystianingrum, Vita (Department of Electrical Engineering ITS and FORTEI, 2023)
Educational buildings have the potential to support government programs in efforts to reduce carbon emissions. Installing photovoltaics and providing charging stations can reduce the use of fossil fuels and increase the number of electric vehicle users. This paper aims to optimize educational buildings when implementing a prosumer scheme and integrating Plug-in Electric Vehicles (PEV) to meet building electricity demands. Optimization is carried out through two case studies, namely the application of a prosumer scheme with independent photovoltaic generators with and without PEV integration. The optimization process uses the Modified Firefly Algorithm. The results obtained by applying the prosumer scheme to educational buildings, the two case studies can produce LCOE cheaper than just buying electricity from the grid. Optimizing results show that photovoltaic installation and charging stations in educational buildings can be beneficial when implementing a prosumer scheme.